Hubungan stres dengan sokongan di persekitaran kerja di kalangan guru sekolah menengah - Chan, Nelee (1998)
The purpose of this study was to investigate the relationship between stress and support in the working environment among secondary school teachers. This study was also aimed at finding teachers level of stress and to determine if they were differences in teachers stress and teachers demographic characteristic namely sex, school grade, school location, race, age, teaching experience academic qualification and number of teaching periods. Then, this study will attempt to examine the relationship between stressors and support in school with teacher's stress.